The Effectiveness of Marital Group Counseling on Happiness and Self-Compassion in Couples with Marital Conflict - Amin Anaraki, Farbod; Biglari, Fatemeh; Hasani, Masoumeh; Tarshayeh, Saeedeh Esmaeilzadeh; Allah Gholipour, Saba; Jafari, Soheil (Mental Health and Lifestyle Journal, 2025)
This study aimed to investigate the effectiveness of systemic group marital counseling on enhancing self-compassion and happiness in couples experiencing marital conflict. The research employed a quasi-experimental design with a pre-test–post-test and two-month follow-up, including a control group. Thirty couples with diagnosed marital conflict were selected using convenience sampling from counseling centers in Tehran in 2024 and randomly assigned to experimental and control groups. The experimental group participated in eight 90-minute sessions of systemic group marital counseling based on family systems theory, while the control group received no intervention. Assessment tools included the Self-Compassion Scale (Neff, 2003) and the Oxford Happiness Questionnaire. Data analysis was conducted using SPSS-26, employing repeated measures ANOVA to examine intra-group and inter-group differences over time. The results indicated significant improvements in both self-compassion (p = .008) and happiness (p = .024) in the experimental group compared to the control group. Within-group analysis revealed that changes in self-compassion and happiness across the three phases (pre-test, post-test, follow-up) were statistically significant (p < .001), with large effect sizes for both variables. The interaction effect between time and group was also significant (p < .001), indicating that the intervention had a sustained impact over time. Systemic group marital counseling proved to be an effective intervention for improving self-compassion and happiness in couples facing marital conflict. The therapeutic emphasis on restructuring family dynamics, enhancing communication skills, and fostering emotional differentiation contributed to significant improvements in psychological and relational well-being. These results support the integration of structured group counseling approaches in clinical and community settings as a cost-effective and impactful modality for addressing marital distress.